Electroforming-based micro-texturing: Advancements for surface engineering in EDM - Mariana Hernández-Pérez; Pedro M. Hernández-Castellano; Juan M. Vázquez-Martínez; María D. Marrero-Alemán (Heliyon)
In the domain of surface engineering, certain additive manufacturing technologies have established themselves as efficient and sustainable solutions. Mask stereolithography (MSLA) has gained prominence, especially when combined with the electroforming process for the production of microtextured copper electrodes. These electrodes are of particular interest in die sinking EDM (SEDM) applications, where high precision in geometry and microtextures is required, and alternative manufacturing technologies often struggle to meet these demands. This study presents the development of microtextured electrodes for sinking EDM processes (SEDM), fabricated by mask stereolithography (MSLA) and copper electroforming. The process starts with the design of textured 3D models using CAD software, followed by their fabrication with MSLA, using high-resolution photosensitive resins. Subsequently, the parts are metallized by sputtering to give them electrical conductivity and, finally, they are subjected to an electroforming process in an electrolytic bath to generate the copper shells. Finally, a metrological characterization was carried out at each stage of the process, from CAD design to the final part obtained by EDM, evaluating textures in low and high relief. The results demonstrate high replicability in the transfer of microtextures to electroformed shells. However, some dimensional variations are observed, primarily due to the inherent limitations of the resolution of MSLA technology. For biomimetic textures, such as those inspired by shark skin, excellent lateral fidelity was observed, while low-relief geometric textures presented greater variations due to the accumulation of photosensitive resin in the first layers of the texturing. Post-processing, particularly thorough cleaning using advanced techniques such as ultrasonic cleaning, proved crucial in minimizing dimensional errors and improving final accuracy. These findings provide a solid foundation for the development of future research aimed at optimizing the accuracy of electrode texturing for EDM applications, addressing a critical need in the field of functional surface microfabrication.